Impactos da educação empreendedora na visão de carreira profissional futura: um estudo com alunos concluintes do ensino fundamental da rede municipal de ensino de São José dos Campos/SP - Aline Campos Figueiredo (2012)
This study aimed to analyze the relationship between entrepreneurial education and the elementary school graduates career vision of the Municipal Public Schools of São José dos Campos, São Paulo, Brazil. To achieve this goal the theoretical framework was based the concepts of types of careers, entrepreneurship and entrepreneurial education. Was chosen conducting quantitative research, which instrument was a questionnaire developed based on the hypothetical theory model for the proposed research. The collected data were tabulated and analyzed by using descriptive statistics and multivariate analyzes that included the factor that enabled the validation of the psychometric scales used in the survey instrument. Furthermore, application of the method enabled by Structural Equation evaluate the degree of importance that each variable interfered with each construct, as well as the calculation of the respective coefficients path, set by the relational model between Entrepreneurial Education and Types of Professional Career Vision. Among the main conclusions of the study is the confirmation of nomological-structural model validity. This means that in the perception of the senior students of the elementary education of Municipal Education of São José dos Campos who composed the study sample, Entrepreneurial Education has a positive and significant relationship with the Modern /Protean Career so as with Traditional Career. However, the relationship with the Entrepreneurial Education and the Modern / Protean Career is more intense compared to the Traditional Career. What comes finally confirm the theory studied and the expectation taken for research.